The Effect of Implementing the Talking Stick Method on Mastering Ilm al-Sarf in the First Grade at Wali Songo Islamic Institute - Nurul Azizah; Muhammad Sayifullah; Dian Risky Amalia (Lisan An Nathiq : Jurnal Bahasa dan Pendidikan Bahasa Arab, 2026)
This study was conducted in response to the low level of understading of ilm al-sarf among fisrt-level studens in Islmaic Boarding School environments. The aim of this research is to determine the effect of using the "talking stick" method on improving students comprehension of ilm al-sarf. This study employed a quantitative approach using a quasi-experimental design with a control group, pre-test, and post-tests. The validity of the research instrument was confiirmed, as the calculated "r" value exceeded the value (0.361) at a significance level of 0.05. The analysis showed that the data were normally distributed (p-value = 0.200 > 0.05). The t-test results indicated a significant effect in the experimental group (p-value = 0.000 < 0.05), while the control group showed no statistically significant difference (p-value = 0.136 > 0.05). Therefore, the Talking Stick method was proven effective in enhancing students' understanding of ilm al-sarf at the first level of learning.